Bacterial endocarditis following repeated tattooing. Issue 1 (1st January 2001) - Satchithananda, D K; Walsh, J; Schofield, P M
Abstract : Body decoration in the form of tattooing is becoming increasingly popular, especially among younger age groups. Although serious infections following tattooing are rare they are well documented. The first reported case of endocarditis caused by repeated tattooing in an individual with known valvar heart disease is presented.